Separation of abnormal cells in the peripheral blood by means of the zonal centrifuge - Egan, Patricia M. (1974)
The basic principles of rate centrifugation in the large volume zonal centrifuge and its application to the separation of abnormal or rarely occurring cells in the blood are described. Details of the method, gradient media, and collection and examination of the fractions obtained are given. A description of the cells found in normal human blood, in a subject undergoing known immunological stimulus, and in glandular fever and Hodgkin's disease is given and the implications are discussed.